Socialcar
Project
Sign in
Ask The Question
English
French
Spanish
Portuguese
Polish
Romanian
Mathematics
emilymetcalf
Oct 9, 2018, 11:45:40 PM
39
what is the answer to x-(9x-10)+11=12x+3(-2x+1/3
+3
(
1
) Answers
jessicafreeman6
Oct 10, 2018, 4:31:40 AM
x = 10/7. Hope this helped
Add answer
Sign in
Sign up
Related Questions
what is the answer to x-(9x-10)+11=12x+3(-2x+1/3
x-(9x-10)+11=12x+3(-2x+1/3)
x-(9x-10)+11=12x+3(-2x+1/3)
What is the solution to the equation 1/3(9x - 6) = 2x 3 ? x =
what is the answer to 2x=x^2-3
What is the answer to 2x 3 < x 5?
What is 7x+9x to the second power minus 12x+3
What is the quotient (2x^2 + 12x + 18) ÷ (x + 3)? 2x + 6 2x − 6 2x + 4 2x − 4, r = 1
what is the answer to 2/3 (x +2) -1/3(x-2)
what is the answer to -3(z+1)+11<-2(z+13)